Schizophrenia : gender differences in diagnosis and mortality in admitted patients - Høye, Anne (2012)
The papers of this thesis are not available in Munin: 1. Høye A, Hansen V, Olstad R: 'First-admission schizophrenic patients in northern Norway, 1980-95 : Sex differences in diagnostic practice', Nordic Journal of Psychiatry (2000) vol. 54, no. 5:319-325. Available at http://dx.doi.org/10.1080/080394800457147 2. Høye A, Rezvy G, Hansen V, Olstad R: 'The effect of gender in diagnosing early schizophrenia : an experimental case simulation study', Social Psychiatry and Psychiatric Epidemiology (2006), vol. 41, no. 7: 549-555. Available at http://dx.doi.org/10.1007/s00127-006-0066-y 3. Høye A, Jacobsen BK, Hansen V: 'Increasing mortality in schizophrenia : are women at particular risk? : a follow-up of 1111 patients admitted during 1980-2006 in Northern Norway', Schizophrenia Research (2011), vol. 132, no 2–3:228–232. Available at http://dx.doi.org/10.1016/j.schres.2011.07.021